2017
DOI: 10.1111/ajad.12635
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of response to sertraline versus placebo among recently abstinent, cocaine dependent patients: A retrospective analysis of two clinical trials

Abstract: Background and Objectives Moderators of treatment response to serotonin reuptake inhibitor sertraline (SRT) for cocaine dependence were assessed in two randomized, double blind, placebo-controlled clinical trials. Methods Generalized estimating equation modeling was performed on data from cocaine-dependent volunteers randomized to receive SRT or placebo (N=126) who completed ≥ 2-week drug-free residential portions of the 12-week trials, in which subsequent outpatient treatment (weeks 3–12) included weekly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In contrast, Kennedy et al 45 reported that in polydrug (cocaine+heroin) users, women undergoing opioid agonist therapy showed higher relapse over a 7-month period. However, during 3-month 50,51 and 6-month 52 treatment follow-up, women showed lower relapse rates. Similarly, when relapse was assessed at treatment follow-up, women often exhibit better outcomes.…”
Section: Relapsementioning
confidence: 85%
“…In contrast, Kennedy et al 45 reported that in polydrug (cocaine+heroin) users, women undergoing opioid agonist therapy showed higher relapse over a 7-month period. However, during 3-month 50,51 and 6-month 52 treatment follow-up, women showed lower relapse rates. Similarly, when relapse was assessed at treatment follow-up, women often exhibit better outcomes.…”
Section: Relapsementioning
confidence: 85%